Female Agency in Popular Music: Desire and Self-control in Selena Gomez’s Song “Can’t Keep My Hands to Myself” - Syarifah, Syarifah; Manugeren, M.; Barus, Efendi (Universitas Pahlawan Tuanku Tambusai, 2025)
Popular music stands as a cultural space where emotion, identity, and power intertwine. Within this realm, female voices often perform the delicate balance between desire and restraint. Yet, few studies have examined how mainstream pop songs articulate female desire beyond objectification, particularly in the work of Selena Gomez, whose music navigates intimacy and autonomy with subtle complexity. This study examines Selena Gomez’s “Can’t Keep My Hands to Myself” to explore how female agency emerges through the negotiation of longing and self-control. Employing a feminist literary lens and Freud’s psychoanalytic framework of the id, ego, and superego, the analysis reveals how sensual impulse and conscious regulation coexist in lyrical expression. In dialogue with Cann (2021) and Jansson (2021), the study interprets the song as a declaration of embodied autonomy, where sensuality becomes self-possession rather than submission. Through qualitative content analysis, the findings affirm that pop music offers a stage for reimagining female identity—where emotion, restraint, and power converge in a harmony of self-aware desire.